Haplophytin B from maclurodendron porteri - Bakhtiar, M. Taher; Darnis, Deny Susanti; Abd Hamid, Shafida; Edueng, Khadijah; Md. Jaffri, Juliana; Adina, Anugerah; Rezali, Mohd Fazlin (Faculty of Pharmacy, University of Karachi, 2014)
An alkaloid from Maclurodendron porteri has been isolated and characterized. Extraction process was conducted by acid-base extraction method followed by column chromatography. The structure was established by nuclear magnetic resonance spectroscopy and mass spectrometry. The compound was identified as haplophytin B which occurs commonly in the Rutaceae family. However, this is the first time this alkaloid was isolated and reported from the species. The compound showed no inhibition against Staphylococus aureus, Pseudomonas aeruginosa, Bacillus cereus and Escherichia coli and no cytotoxic activity against H199 and A549 cell lines.